Surface roughness of supra-nano spherical filled and nanohybrid composite resin after Coffea arabica immersion: an experimental study - Jordan, Bryan Matthew; Ratnasari, Dina; Fibryanto, Eko; Bin Azman, Syuwari Azhar (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Supra-nano spherical filled composite resin (Omnichroma, Tokuyama, Japan) with sol-gel method has 0.26 μm filler size, while nanohybrid composite resin (ENA HRi, Micerium, Italy) has 0.2-1 μm filler size. Nanofillers enhance resistance from chlorogenic acid contained in Coffea arabica. This study analyzed the surface roughness difference between supra-nano spherical-filled and nanohybrid composite resins after Coffea arabica immersion for 7 and 14 days, with 15 minutes of immersion each day. Methods: This study was an in vitro laboratory experiment with a pretest-posttest control group design. Twenty composite resin samples were immersed in artificial saliva and divided into four groups; supra-nano coffee, nanohybrid coffee, supra-nano saliva (control), and nanohybrid saliva (control). After 24 hours, immersion in Coffea arabica was started for supra-nano coffee group and nanohybrid coffee group for 15 minutes daily until days 7 and 14. Control groups were immersed in saliva. Results: One-way ANOVA showed significant differences in the surface roughness between composite resin groups. Post-hoc Tukey showed a significant difference between supra-nano coffee (0.91± 0.29 μm) and nanohybrid saliva (1.43±0.42 μm). The GLM Repeated Measure test showed significant surface roughness changes in supra-nano after 14 days of immersion in Coffea arabica (1.47±0.13 μm), while nanohybrid experienced surface roughness changes in 7 days of immersion in Coffea arabica (1.94±0.55 μm) and increased in 14 days (2.25±0.47 μm). In saliva immersion (control group), nanohybrid experienced an increase in surface roughness after 14 days, while supra-nano did not experience a significant increase in surface roughness. Conclusion: Supra-nano spherical filled composite resin exhibits greater resistance to changes in surface roughness following immersion in Coffea arabica.KEYWORDSCoffea arabica, nanohybrid, composite resin, supra-nano spherical filled, surface roughness